Los periplos de Eudoxo de Cízico en la Mauretania Atlántica - Mederos Martín, Alfredo; Escribano Cobo, Gabriel (Gerión. Revista de Historia Antigua, 2005)
The four trips of Eudoxus of Cyzicus, tried to acceding to the spices trade, aromatic plants and precious stones of India, two times as egyptian royal expeditions, before 116 B.C. and ca. 111-110 B.C., from the Red Sea toward the Indian Ocean, taking advantage the monsoon in a high sea navigation, and two times from Gadir, ca. 108-107 B.C. and 105-104 B.C., attempting to border an African continent that is believed of much smaller dimensions, because were thought that the Cape Guardafui of Somalia was the Horn of the South. The third trip did not have to surpass the river Drâa in Morocco * Departamento de Prehistoria de la Universidad Complutense de Madrid. Facultad de Geografía e Historia. Ciudad Universitaria. 28.040 Madrid. & Department of Anthropology, Peabody Museum, Harvard University, 11 Divinity Avenue, Cambridge, Massachusetts, 02138-2019. ** Programa de Doctorado. Departamento de Prehistoria, Antropología e Historia Antigua. Facultad de Geografía e Historia. Universidad de La Laguna. Campus de Guajara. 38071 La Laguna. Tenerife. Gerión ISSN: 0213-0181 2004, 22, núm. 1 215-233 Alfredo Mederos Martín, Gabriel Escribano Cobo Los periplos de Eudoxo de Cízico en la Mauretania Atlántica and the river Seguia el-Hamra in Western Sahara, with black populations of dararites Ethiopians. In the return of the third trip, also a high sea navigation, he had to be approximated to an island of the Western Canaries or Fortunatae Islands, with abundant vegetation and water, and after stopped over in Mauretania. There he visited to king Bocchus I, in full Yugurtan War (112-105 B.C.), who planned to abandon him in an island or small islet of the Eastern Canaries to avoid a possible Roman presence in waters to the South of his kingdom. Of the result of the fourth trip is not known if he returned, though Eudoxus drafted, perhaps after of the third trip, a text on India that was including data of the Ethiopian populations.
Keywords: Eudoxus of Cyzicus; India; spices trade; Gadir; Mauretania; Bocchus I; Yugurtan War; Canary Islands